2012
DOI: 10.3168/jds.2011-5226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding dairy cows different legume-grass silages on milk phytoestrogen concentration

Abstract: Phytoestrogens are hormone-like substances in plants that can substantially influence human health (positively or negatively), and when fed to dairy cows are partly transferred to their milk. The aim of this study was to investigate the effects of varying the botanical composition and regrowth interval of legume-grass silage on phytoestrogen intake and milk phytoestrogen concentrations. In one experiment, 15 Swedish Red dairy cows were fed 2- or 3-cut red clover-grass silage, or 2-cut birdsfoot trefoil-grass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
46
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 44 publications
13
46
0
6
Order By: Relevance
“…For instance, it is well established in human populations $20-30% of individuals can produce equol at relatively low concentrations compared to animals (Frankenfeld, 2011;Lephart, 2013a;Setchell & Clerici, 2011) and recent evidence indicates that equol is present in plant products such as beans, cabbage, and lettuce (Hounsome et al, 2009(Hounsome et al, , 2010. Further research has revealed that equol concentrations in low-soy consuming US populations reflect equol intakes from mammalian (cow) milk sources (Frankenfeld, 2011;Hoikkala et al, 2007;Mustonen et al, 2009) that can be as high as 1.5 mg/kg in cow's milk (Höjer et al, 2012). Notably, the metabolism of Rand S-equol in humans appears to be similar (Setchell et al, 2005(Setchell et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is well established in human populations $20-30% of individuals can produce equol at relatively low concentrations compared to animals (Frankenfeld, 2011;Lephart, 2013a;Setchell & Clerici, 2011) and recent evidence indicates that equol is present in plant products such as beans, cabbage, and lettuce (Hounsome et al, 2009(Hounsome et al, , 2010. Further research has revealed that equol concentrations in low-soy consuming US populations reflect equol intakes from mammalian (cow) milk sources (Frankenfeld, 2011;Hoikkala et al, 2007;Mustonen et al, 2009) that can be as high as 1.5 mg/kg in cow's milk (Höjer et al, 2012). Notably, the metabolism of Rand S-equol in humans appears to be similar (Setchell et al, 2005(Setchell et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Moorby et al (2004) found that lambs grazing red clover with high concentrations of formononetin had slightly higher daily weight gains than lambs grazing red clover with lower formononetin concentrations or perennial ryegrass, with the same daily dry matter intake. Additionally, phytoestrogens, when red clover containing diets (grazing pastures or silage) are fed to dairy cows are partly transferred to their milk (Höjer et al, 2012;Adler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Silages prepared from primary growth of a mixture of timothy-meadow fescue (Festuca pratense) contained no isoflavones (Mustonen et al, 2009). Also data of Höjer et al (2012) prove that red clover is the main source of isoflavones in silages of legume-grass mixtures (Table 4).…”
Section: Isoflavones In Foragesmentioning
confidence: 95%